CAUSAL FACTORS ANALYSIS OF MATHEMATICS LEARNING DIFFICULTIES IN 4TH GRADE STUDENTS - Utami, Anajulia Putri; Ermawati, Diana; Riswari, Lovika Ardana (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
Learning difficulty means students cannot learn well in an academic field. One of the learning difficulties experienced by students is mathematics, especially the material of small numbers. So, the focus problem of this research is the factors that cause learning difficulties. This research aims to discover the factors of learning difficulties in mathematics in the material of integers in 4th grade students at SD 1 Bakalan Krapyak. This research uses a narrative-oriented qualitative approach. The results prove that the factors that cause student learning difficulties consist of several levels, namely T1 level students with factors that affect learning ability, health, learning environment, and the learning process provided by the teacher. The influencing factors of T2 students are interest in learning, health, classroom environment, and family. The factors that affect S1 students are health and classroom environment. S2 students are interested in learning interest and the classroom environment. R1 students have learning interests, health, classroom environment, and family. R2 students have factors influencing learning difficulties: intelligence, health, classroom environment, and family. So, it is concluded that the factors that cause learning difficulties include internal and external factors. Internal factors are learning ability, interest in learning, health, and individual intelligence. External factors are the classroom environment, including the state of the learning process and the family environment.